Developing and piloting location-specific fertilizer recommendation for wheat in Ethiopia - Liben, Feyera M.; Abera, Wuletawu; Ebrahim, Mohammed; Tilaye, Amsalu; Erkossa, Teklu; Kebebe, Firew; Bogale, Beza; Girmaw, Mekdes; Ayele, Kebede; Tamene, Lulseged D. (2022)
This report covers the progress of developing and piloting location-specific fertilizer and agroclimate advisory service for Wheat in Ethiopia. The report highlights the major activities implemented during the 2022 cropping season including (1) review of organic fertilizer recommendations for wheat; (2) generation of location-specific fertilizer rate (LSFR) for piloting; (3) developing kebele map for LSFR recommendation; (4) video preparation for demo training; (5) trainings organized on piloting LSFR advisory and map reading; (6) LSFR advisory reach and adoption; (7) Alliance and partners pilot trial field visits during the main wheat season; (8) field days organized ; and (9) certificate of appreciation awarded to Alliance and its partners. The main purpose of the report is to narrative the processes associated with the development of agroadvisory and its piloting in the highlands of Ethiopia.